Pendidikan Agama Islam sebagai Pendekatan Psikoedukatif dalam Menangani Isu Kesehatan Mental Remaja di SMA - Rafiq, Muhammad Ainur; Surawan, Surawan (TSAQOFAH, 2025)
Adolescence is a complex developmental stage marked by heightened vulnerability to psychosocial stress, necessitating an educational approach that addresses not only cognitive but also emotional and spiritual dimensions. Islamic Religious Education (Pendidikan Agama Islam/PAI) plays a strategic role in fostering adolescent mental resilience through a psychoeducational approach integrated with spiritual, moral, and social values. This article aims to analyze the contribution of PAI to adolescent mental health at the senior high school level using a qualitative case study approach. The focus of the study includes three main aspects: stress management, confidence building, and the development of social support through religious communities. The findings show that PAI effectively assists adolescents in managing stress through the internalization of Islamic values such as sabar (patience) and tawakal (trust in God), enhances self-confidence through an understanding of individual potential as God's creation, and strengthens social support through participation in collective religious activities. These results are supported by previous studies indicating that active involvement in religious practices positively impacts emotional stability, inner peace, and identity formation. Therefore, PAI should be positioned not merely as a normative subject, but as a transformative educational instrument that holistically supports the psychological well-being of adolescents.